Demystifying Dividend Yield: Unveiling the Impact of Financial Metrics in Malaysia's Top 100 Ranked Companies - Amir, Aliana Shazma; Quayyum, Che Muhammad; Md. Isa, Evawaynie Valquis; Zaidi, Zulaikha Rabitah (Universitas Medan Area, 2024)
This research examines the complex link that exists between dividend yield and return on assets (ROA), audit quality, business size and liquidity among Malaysia's top 100 ranked companies in 2022. A statistically significant positive correlation has been shown between ROA and dividend yield, suggesting that increased profitability is generally associated with larger dividend yields. This research lends credence to the signaling theory, which holds that companies use their dividend policy to communicate to investors their financial stability and confidence. In a similar vein, there is a notable positive correlation between AQ and dividend yield, which emphasizes the importance of strong audit procedures in boosting investor trust and raising dividend payments. Additionally, the research reveals a noteworthy affirmative association between firm size and dividend yield, underscoring the influence of market capitalization on the determination of dividend policy. Consistent with signaling theory, larger corporations use dividends as a strategic way to communicate their commitment to shareholders because they are seen as more financially reliable. Furthermore, a strong positive correlation has been shown between liquidity and dividend yield, highlighting the crucial role liquidity plays in determining dividend payout policies and providing investors with a sense of financial safety. This study, which makes use of signaling theory, sheds light on how businesses strategically employ dividend policy to convey important information to the market, boosting investor confidence and improving market repute. The practical ramifications of these findings include enlightening investing strategies and giving investors insight into the factors influencing decisions about dividend policy. Theoretical contributions include deepening our understanding of the intricate relationship between dividend policy and financial indicators in the context of signaling theory and providing insightful information for further study.